ВИЛЬГЕЛЬМРАМЗАИТ, CU3FES3 ∙ 2Н2О - НОВЫЙ МИНЕРАЛ ИЗ ХИБИНСКОГО МАССИВА, КОЛЬСКИЙ ПОЛУОСТРОВ - Пеков И.В.; Чуканов Н.В.; Болдырева М.М.; Дубинчук В.Т. (My University, 2006)
A new mineral wilhelmramsayite was found in the core of hyperagpaitic pegmatite at Koashva Mt, in Khibiny alkaline massif. It is associated with villiaumite, thermonatrite, pectolite, aegirine, microcline, sodalite, lomonosovite, chkalovite, sphalerite, rasvumite, etc. It occurs as flattened on {001} rectangular lamellar and tabular crystals up to 1 X 5 X 6 mm in size. Opaque, luster metallic, color dark lead-grey; in moist air, wilhelmramsayite becomes iron-black; streak black. Cleavage on (001) perfect mica-like, fracture laminated. Mohs hardness 2.5, micro-indentation hardness 111-122 (mean 116) kg/mm2 D(meas.) 2.75, D(calc.) 2.84 g/cm3. In reflected light, it is bluish-grey, bireflectance weak. Pleochroism weak, from bluish grey to grey with slight bluish tint. Anisotropy weak, with bluish and brownish rotation colors. No internal reflections. Reflectance values [R1- R2, % (λ, nm)] are: 18.35-20.25 (470), 14.4-16.85 (546), 12.4-14.7 (589), 10.35-12.65 (650). The IR spectrum shows a presence of H2O molecules and absence of (OH) groups bonded with cations. Chemical composition (electron probe, H2O by TGA; wt %) is: Na 0.12, К 0.27, Tl 0.44, Cu 48.52, Fe 15.20, S 25.20, H2O+ 9.28, H2O- 1.43, total 100.46. The empirical formula calculated on S3 (without H2O-) is Cu2.91Fe1.04S3.00 (K0.03Na0.02Tl0.01)Σ0.06(H20)1.97. The simplified formula (Z= 1) is Cu3FeS3 ∙ 2H2O. From the electron diffraction data, wilhelmramsayite is orthorhombic, space group Pmmm. Unit cell dimensions refined from the powder data are: a = 5.147(2), b = 7.289(2), с = 5.889(3) Å, V= 220.9(2) Å 3. The strongest reflections of the X-ray powder diagram (d, Å - I[hkl]) are: 5.12-40[100], 4.21-40[110], 3.69-30[20], 3.104-100[21], 2.727-50[012], 2.292-50[022], 1.985-30[221, 003], 1.897-70[013], 1.828-50[103, 040]. The crystal structure is apparently layered, with H2O molecules in the interlayer space. Probably, wilhelmramsayite was formed by the hydration of hypothetical protophase [(K,Tl)xNay]Cu3FeS3. The mineral is named in the memory of Wilhelm Ramsay (1865-1928), an outstanding Finnish geologist, mineralogist and petrographer who completed first detailed study of the Khibiny-Lovozero alkaline complex. The type specimen is deposited in Fersman Mineralogical Museum of the Russian Academy of Sciences, Moscow.
Keywords: 549.331(470.21)